Comunidade de algas perifíticas em substrato artificial no Rio Água Limpa e Lago dos Tigres (Britânia-GO) durante dois períodos de águas baixas - Rodrigues, Juliana (2007)
Periphyton algae community on slides glasses at Água Limpa River and Lake of Tigres (Britânia, State of Goiás, Brazil) during two low waters periods. The aims of this dissertation was analyze the community of periphytic algae of Lake of Tigres (15°36"33,1''S/ 51º17'55,7''W) and Agua Limpa river (15°36"33,5''S / 51º17'56,3'' W ). Both environment belong the Tocantins-Araguaia basin and have differents water hydrodynamics. The first one is a blocked valley. This study looking for the influence of differents day of artificial substratum disposed in differents moths of low water periods (dry and beginning of the rain periods) in the first chapter and colonization during four weeks in dry period of 2005 in the second one. Were collected informations about climatic variables (temperature of air, pH, conductivity, turbidity, total dissolved solids, dissolved oxygen, total nitrogen and total phosphorous). The synthesis of limmnologicals variables was made by principal components analysis (PCA) and the synthesis of limnological and periphyton algae community were made by canonical correspondence analysis (CCA) and dissimilarity analysis (WPGMA) In the firs part of the study (2004) the artificial substratum were exposed during 20 until 37 days, both environments studied had high level of dissolved oxygen and water temperature, low level of nutrients and pH between alkaline and acid. Still had 67 taxa the majority was microperiphytics and ordinary species, high diversity and density tendency the β diversity had tendency to be homogeneous. The diatoms, R and S-selected taxa group were predominant in both sample stations. Only two species were dominant taxa (Navícula sp1- A1; Pinularia flexuosa - N2) and 34 were abundant. CCA characterized phosphorous and R-estratgist algae and Pseudoanabaena sp1, Surirella sp2, Oedogonium sp1, Cosmarium sp1, Cosmarium sp4 e Diploneis subovalis how the most important descriptors of the community of periphytic algae. In 2005, the artificial substratum that were exposed only in Agua Limpa River during four weeks and removed in 4th , 6th , 8th , 17th and 30th days, the water had high level of oxygen, nutrients and water temperature. Were registered 121 taxa, the majority micoperiphytic, ordinary species and diatoms. Were found high density and specific diversity. The β diversity was homogeneous specific composition, 72 abundant species, R and S-selected taxa group, and diatoms were representatives during the study, especially in richness and density. Both samples stations had same specific composition and functional group because de very closes geographic area. At the end of the study were detected the principal explanations of the periphyton algae community were made by R and S-selected taxa of functional group, Bacillariophyceae, high diversity and density and Total phosphorous.